The Application of Restorative Justice for Children as Criminal Offenders in the Perspective of National Law and Qanun Jināyat - Rizanizarli, Rizanizarli; Mahfud, Mahfud; Pratama, Riza Chatias; Fikri, Fikri (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This study aims to examine the application of restorative justice to children as criminal offenders based on the 2012 SPPA Law and the 2014 Qanun Jināyat. This study is an empirical legal study using a statutory approach and restorative justice theory. Data collection techniques were carried out through in-depth interviews and literature studies. The results of the study show that Article 5 paragraph (1) of the 2012 SPPA Law stipulates that if a child commits a crime or jarīmah, a restorative justice approach must be prioritized, and in Article 7 paragraph (1), it is stated that at investigation, prosecution, and examination level of a child's case in the district court, it is mandatory to attempt diversion. The Qanun Jināyat of 2014 does not separately regulate the settlement of children who commit crimes. However, it designates laws and regulations regarding juvenile justice. Qanun Jināyat regulates the handling of children who carry out a jarīmahikhtilaṭ to carry out an examination guided by the law mentioned above. However, in the case of children who commit crimes of ikhtilaṭ and are investigated by the police, the process is carried out in a restorative justice and diversionary manner. The forms of settlement in restorative justice are reconciliation with or without compensation, return to parents or guardians, social rehabilitation, and religious rehabilitation. This study argues that restorative justice treats children in a dignified manner oriented towards juctice and the interests of the child. Likewise, the study shows that SPPA Law and Qanun Jināyat complement each other.